In situ synthesis of V2O3 nanorods anchored on reduced graphene oxide as high‐performance lithium ion battery anode. Issue 43 (19th November 2018) - Liu, Xiaoqing; Zhang, Dan; Li, Guangshe; Xue, Chenglin; Ding, Junfang; Li, Baoyun; Chen, Dandan; Li, Liping
Abstract: The potential applications of V2 O3 in lithium ion batteries (LIBs) are significantly hampered by the comparatively poor rate performance as well as fast capacity decay due to the low electrical conductivity and huge volume change during cycling process. Various strategies have been proposed to address these drawbacks. Among different methods, reducing their particle size to the nanometer range and combining with carbonaceous matrix seem to be effective ways to improve electrochemical property. Herein, we prepared V2 O3 nanorods in‐situ adhered to rGO via hydrothermal reaction and heat‐treatment. One dimensional V2 O3 nanorods combined with rGO can effectively shorten Li + ions and electrons transport path, improve electrical conductivity and alleviate volume change. The strong chemical interaction between them would remarkably accelerate charge transfer. These features endow V2 O3 /rGO composite with good cycling stability (675 mA h g −1 after 300 cycles at 500 mA g −1 ) and excellent rate performance (428 mA g h −1 at 2000 mA g −1 ). New prospects will be brought by this work for the potential application of V2 O3 based material as advanced anode material for LIBs. Abstract : The V2 O3 /rGO composite was synthesized by a facile method. One‐dimensional V2 O3 nanorods are grown in situ on rGO. Unique nanostructure leads to the excellent electrochemical performance. High capacity of 675 mA h g −1 after 300 cycles is achieved at 0.5 A g −1 .